COLLABORATION ON DEVELOPMENT PLANNING POLICY: MITIGATION OF ABRASION PREVENTION IN SIAK REGENCY (CASE STUDY OF MENGKAPAN VILLAGE) - Ali Asfar; Indra Suandy; Yusri Yusri; Agus Mandar; Maellynia Mustofa (Asian Journal of Aquatic Sciences, 2025)
Siak Regency, located in Riau Province, is one of the areas facing a serious threat of abrasion, especially in coastal areas bordering the Lalang Strait. Mengkapan Village, one of the coastal villages in Siak Regency, has been significantly affected by abrasion. Based on initial observations, the abrasion rate in this area is 2-5 m per year, which poses a threat. Development planning policies play a crucial role in addressing the abrasion phenomenon in Mengkapan Village, Siak Regency, Riau Province. With good planning, development will align with community expectations. Based on satellite imagery analyses in 2020 and 2025, Mengkapan Village experienced abrasion at a rate of 6.43 m/year. Development planning policies in coastal abrasion mitigation must be an integral part of a sustainable regional development strategy. Through a combination of structural, non-structural, and collaborative approaches, along with strong policy support, coastal abrasion can be minimized. Synergy among the government, community, business world, and academia are key to realizing a resilient, productive, and sustainable coastline for future generations.